Aplikasi Permainan 2D Perang Tondano Berbasis Role Playing Game (RPG) - Tular, Feonri; Moningkey, Efraim Ronald Stefanus; Santa, Kristofel (JOINTER : Journal of Informatics Engineering, 2025)
This research aims to develop a Role-Playing Game (RPG) that highlights the history of the Tondano War to enhance the understanding of young generations. The Game Development Life-Cycle (GDLC) method was employed, consisting of five stages: initiation, pre-production, production, testing, and release. Data collection involved literature review and observation, with the game tested through blackbox testing on Android and Windows platforms. The results show that the game successfully introduces the history of the Tondano War through interactive narratives presented in chapters of varying difficulty. The game also allows players to strategize in turn-based combat. In conclusion, this game is effective as an educational medium that enriches historical knowledge and offers an engaging experience for young players.